Why India Is Not Quite a Part of the Asian Miracle. (January 2020) - Desai, Meghnad
This paper seeks to explain the low growth trajectory of India vis-a-vis East Asia in a historical and cultural perspective. It is argued that the Indian subcontinent was culturally separated from Buddhism and therefore from an egalitarian social possibility after the first millennium CE. A brief history of Indian economic development since independence is provided in light of the introductory historical account. JEL: N15, O10, O53